PERSAINGAN PORTAL BERITA ONLINE MENGGUNAKAN PRESPEKTIF TEORI NICHE PADA KAJIAN EKONOMI MEDIA - Annisa Rizki Ananda; Rachmat Kriyantono; Antoni Antoni (Metacommunication: Journal of Communication Studies, 2020)
Online news portals are interesting objects to study because they are superior to traditional media. The presence of the web, makes many researchers see the emergence of new public spaces in which individuals can find and produce diverse information. The development of the media was interestingly researched on seven online news portals which became the pioneers of online media in Indonesia, namely Detik, Kompas, Republika, Okezone, Media Indonesia, Tempo and VIVA . The purpose of this research is to find out media competition by using niche theory perspectives in two aspects namely niche breadt and overlap niche from Detik, Kompas, Republika, Media Indonesia, Okezone, Tempo and VIVA in terms of message distribution. Researchers want to see how competition between online news portals is equally competitive with different media characteristics. The method used first is quantitative content analysis as initial data to calculate niche breadth and niche overlap, second niche breadth analysis, and thirdly niche overlap analysis of the seven online news portals studied.. The results show that media competition in the breadth niche is divided into two generalist parts and tends to be generalist. Generalists point out that online news portals do not depend on a single source of life support. The overlapping niche results show that the level of competition or overlap of the seven online news portals can be said to be high or tight. The high competition category is divided into three parts, namely, the highest, tend to be high and a little high.